2016
DOI: 10.1002/jssc.201600609
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of chiral oxazolinyl-functionalized β-cyclodextrin-bonded stationary phases and their enantioseparation performance in high-performance liquid chromatography

Abstract: Preparation of chiral oxazolinyl-functionalized ␤-cyclodextrin-bonded stationary phases and their enantioseparation performance in high-performance liquid chromatography A simple procedure for the synthesis of three new oxazolinyl-substituted ␤-cyclodextrins (6-deoxy-6-R-(-)-4-phenyl-4,5-dihydrooxazolinyl-␤-cyclodextrin, 6-deoxy-6-S-(-)-4-phenyl-4,5-dihydrooxazolinyl-␤-cyclodextrin, and 6-deoxy-6-S-(-)-(4-pyridin-1-ium-4-methyl-benzenesulphonate)-4,5-dihy-drooxazolinyl-␤-cyclodextrin) and their covalent bondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Li et al [150] arrived at similar conclusions after preparing oxazolinyl-functionalized β-cyclodextrins covalently bonded to silica support (CSP86–88) (Figure 3). They described that analytes with electron-donating or hydrogen-bonding groups were easily enantioseparated due to a higher number of π-π and hydrogen-bonding interactions [150]. CSP88 was more suitable for enantioseparation of polar compounds since it promoted electrostatic interactions due to the presence of an ionic group [150].…”
Section: Chiral Stationary Phases: Recent Developmentsmentioning
confidence: 61%
See 1 more Smart Citation
“…Li et al [150] arrived at similar conclusions after preparing oxazolinyl-functionalized β-cyclodextrins covalently bonded to silica support (CSP86–88) (Figure 3). They described that analytes with electron-donating or hydrogen-bonding groups were easily enantioseparated due to a higher number of π-π and hydrogen-bonding interactions [150]. CSP88 was more suitable for enantioseparation of polar compounds since it promoted electrostatic interactions due to the presence of an ionic group [150].…”
Section: Chiral Stationary Phases: Recent Developmentsmentioning
confidence: 61%
“…It was found that the majority of the new cyclodextrin-based CSPs were prepared based on the most widely used cyclodextrin as CSP, i.e., the β-cyclodextrin [148,149,150,151]. Moreover, the immobilization strategy of the chiral selector on the chromatographic support was, mainly, by click chemistry [149,150,151,152]. The main advantages of this approach are the mild reaction conditions and the enhanced tolerance of the CSPs to solvents and the range of pH values [153].…”
Section: Chiral Stationary Phases: Recent Developmentsmentioning
confidence: 99%
“…Since the shape of truncated hollow cone favor their ability to form stable inclusion with guest molecules [6], cyclodextrins (CDs) are widely used for enantioseparation, especially as CSPs in HPLC [7][8][9][10]. Besides its inclusion features, CDs can be chemically modified to build hydrogen bonding, π-π, steric repulsion interactions, which are all beneficial for chiral recognition process [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, organic silanes with reactive groups have been used to enrich the family of HPLC stationary phases by further derivatization using ligands of suitable size . In some of the new stationary phases, ligands with a synthetic macrocyclic receptor, such as crown ether , cyclodextrin , calixaromatics , sapphyrin , pillararene , and cucurbituril have been tethered with silica. With these new phases, separation of desired solutes can be achieved based on a multiple host–guest recognition interactions.…”
Section: Introductionmentioning
confidence: 99%